2014
DOI: 10.1111/twec.12224
|View full text |Cite
|
Sign up to set email alerts
|

Financial Development and Sustainable Exports: Evidence from Firm‐product Data

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Financial development is the supply of domestic credit from the financial sector to various sectors of the economy except to the central government. It is expected to increase survival rates of exports (Besedeš et al, ; Jaud et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…Financial development is the supply of domestic credit from the financial sector to various sectors of the economy except to the central government. It is expected to increase survival rates of exports (Besedeš et al, ; Jaud et al , ).…”
Section: Methodsmentioning
confidence: 99%
“…It is suggested that countries should consider following the export destination hierarchy which is actually trade cost and the size of market etc. Jaud, Kukenova, and Strieborny (2015) revealed financial development effects on longterm trade and also probed the requirements pertaining to finance at the product level by taking data of firm product export from five countries in the category of development phase. Cross sectional data is employed by using share of exporting country as exogenous variable and limited control as the endogenous variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Berger et al (2013) show that successful CIA interventions in foreign countries lead to dramatic export increases from the US to these countries but have no impact on the exports from the affected countries to the US destination market. 29 Besedes and Prusa (2006a) were the first to apply the analytical tools of survival analysis in the context of international trade, triggering an extensive follow-up research on trade survival (see, e.g., Besedes and Prusa, 2006b;Carballo and Volpe Martincus, 2008;Jaud, Kukenova, and Strieborny, 2009;Nitsch, 2009;Brenton, Saborowski, and von Uexkull, 2010;Obashi, 2010;Besedes and Prusa, 2011;Fugazza and Molina, 2011;Brenton, Cadot, and Pierola, 2012;Carrere, and Strauss-Kahn, 2012;Chen, 2012;Besedes, 2013;Cadot et al, 2013;Jaud, Kukenova, and Strieborny, 2015). 30 In one of the robustness checks in the Online Appendix, we also run a linear probability model of exiting the US destination market as an alternative to the formal survival framework.…”
Section: Empirical Strategymentioning
confidence: 99%
“…This literature has provided empirical support for the importance of wellfunctioning financial environment for countries' and firms' successful export performance in two ways. It has showed that domestic financial development improves export performance, particularly for industries dependent on external finance and firms facing credit constraints (e.g., Beck, 2002Beck, , 2003Ju and Wei, 2005;Greenaway, Guariglia, and Kneller, 2007;Manova, 2008;Jaud, Kukenova, and Strieborny, 2009;Berman and Héricourt, 2010;Becker, Chen, and Greenberg, 2013;Manova, 2013;Besedes, Kim, and Lugovskyy, 2014;Jaud, Kukenova, and Strieborny, 2015). A related strand of papers has explored the negative impact of disturbances in the financial system on trade performance, especially during the recent global financial crisis (e.g., Bricongne et al, 2010;Amiti and Weinstein, 2011;Levchenko, Lewis, and Tesar, 2011;Chor and Manova, 2012;Paravisini et al, 2015).…”
Section: Introductionmentioning
confidence: 99%